Preparation, antioxidant activity, and theoretical studies on the relationship between antioxidant and electronic properties of bis(thio/carbohydrazone) derivatives - Muğlu, Halit; Kurt, Belma Zengin; Sönmez, Fatih; Güzel, Emre; Çavuş, M. Serdar; Yakan, Hasan (Elsevier BV, 2022)
A series of novel bis(thio/carbohydrazone) compounds has been prepared from (thio)/carbohydrazide and various aldehyde derivatives. FTIR, H-1 and C-13 NMR spectroscopy, and elemental analysis have been used to elucidate the structures of synthesized compounds. Their antioxidant properties have been assessed using the DPPH, ABTS, and CUPRAC methods. Most of the synthesized compounds exhibited antioxidant activity in each assay. The effects of the electronic and structural properties of urea/thiourea groups on the antioxidant prop-erties of the compounds have been investigated, and it was observed that thiourea-based compounds showed better antioxidant activity than structurally similar urea-based compounds. Among them, N',N '''-1,4-phenylene-bis(methaneylylidene)-bis(N'-2-hydroxybenzylidene)methane-bis(thiohydrazide) (9) and N '''-(1,4-phenylene-bis(methaneylylidene)-bis(N'-2,4-dihydroxybenzylidene)methane-bis(thiohydrazide) (11) showed higher ABTS activity (IC50 = 2.69 mu M and 3.24 mu M, respectively) than the reference butylated hydroxyanisole (BHA, IC50 = 3.42 mu M). Moreover, compound 11 showed the strongest DPPH activity with an IC50 value of 5.77 mu M, almost twofold higher than that of BHA (IC50 = 9.55 mu M). Structural, spectral, and electronic analyses of the compounds have also been performed by DFT calculations at the B3LYP/6-311++g(2d,2p) level of theory. EDR, NCI, DOS, and QTAIM calculations have been carried out to analyze the bond properties of electronegative atoms and to investigate intramolecular interactions. DFT simulations have also been carried out in order to study the rela-tionship between electronic characteristics and antioxidant activity.
Keywords: Schiff base; Muğlu H., Kurt B., Sönmez F., Güzel E., Çavuş M. S. , Yakan H., -Preparation, antioxidant activity, and theoretical studies on the relationship between antioxidant and electronic properties of bis(thio/carbohydrazone) derivatives-, Journal of Physics and Chemistry of Solids, cilt.164, 2022; Antioxidant activity; Structure elucidation; Carbohydrazones; DFT; Molecular-Structure; Schiff-Bases